Impact of COVID-19 pandemic on overall and examsrelated energy drinks consumption among students of the University of Sarajevo, Bosnia and Herzegovina - Šljivo, A.; Bostandžija, A.; Arnaout, A.; Blekić, A.; Dujić, T.; Aljičević, M.; Tafi, Z.; Skopljak, A.; Kudić, B.; Kusturica, J.; Kulo Ćesić, A. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. A pilot study conducted in academic 2017/18 among undergraduates of the University of Sarajevo showed energy drinks to be most frequently consumed during academic activity, less frequently mixed with alcohol in leisure, and rarely in the sports activity. The aim of this study was to assess the impact of the COVID-19 pandemic on energy drinks consumption among undergraduates of the same University, with a focus on their consumption during exams.Study design. A cross-sectional study was conducted by an online questionnaire.Methods. The questionnaire, mainly based on the Consortium Nomisma-Areté questionnaire, was customized to compare energy drinks consumption before and during the COVID-19 pandemic, and distributed among students between July 26th, 2020 and April 3rd, 2021.Results. Out of 1,045 students who chose to participate in the study (participation rate of 14.7%), 653 students, mostly women, attending the lower study years, reported energy drinks consumption. Both before and during pandemic, overall energy drinks consumption was most frequently reported as rare [281 (43.9%) before, 326 (51.2%) during the pandemic], and exams-related energy drinks consumption as once or twice a week [156 (43.8%) before, 130 (42.1%) during pandemic]. The pandemic increased the number of frequent consumers (consumption of 4–5 energy drinks per week) in both overall [35 (5.5%) before, 46 (7.2%) during pandemic] and exams-related energy drinks consumption [42 (11.8%) before, 48 (15.5%) during pandemic]. Study year (OR=0.842; 95% CI 0.77–0.921; p